ANALYSIS OF DEFIBRILLATION ENERGY EFFECT ON ELECTROCARDIOGRAPH (ECG) - Ardiatna, Wuwus; Hidayat, Siddiq Wahyu; Sadrach, Junaid; Hidayat, Asep Rahmat (Teknologi Indonesia, 2013)
The analysis of determination of defi brillation energy effect on Electrocardiograph (ECG) according to IEC 60601-2-27: 2005 has been conducted in order to measure the energy reduction during defi brillation process on EKG. The result showed the energy differences before and after being connected to ECG was 4,408%.